2001
DOI: 10.1016/s0550-3213(01)00108-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase structure of non-commutative scalar field theories

Abstract: We investigate the phase structure of non-commutative scalar field theories and find evidence for ordered phases which break translation invariance. A self-consistent oneloop analysis indicates that the transition into these ordered phases is first order. The phase structure and the existence of scaling limits provides an alternative to the structure of counter-terms in determining the renormalizability of non-commutative field theories. On the basis of the existence of a critical point in the closely related … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
245
4

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(276 citation statements)
references
References 33 publications
27
245
4
Order By: Relevance
“…Our current data do not address this issue -much larger volumes must be simulated in order to determine whether this phase truly survives the large N limit. Nevertheless, we feel that our simulations lend nonperturbative, albeit qualitative support to the analysis of [1] and [2]. However, it is clearly of more interest to do this in higher dimensional theories.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Our current data do not address this issue -much larger volumes must be simulated in order to determine whether this phase truly survives the large N limit. Nevertheless, we feel that our simulations lend nonperturbative, albeit qualitative support to the analysis of [1] and [2]. However, it is clearly of more interest to do this in higher dimensional theories.…”
Section: Discussionsupporting
confidence: 58%
“…The possibility of having a ground state which breaks translational invariance was first observed in [1]. The quadratic part of the effective action, obtained from (1) by a one-loop self-consistent Hartree calculation, is…”
Section: Stripesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work on these interesting phases of the two-dimensional electron gas has revealed that magnetic symmetry plays a crucial role in low-energy dynamics of these states. Interestingly, recent work on non-commutative field theories has suggested that their phase diagrams involve analogs of these phases [41].…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is to let θ → 0 so thatθ remains fixed. This parameter is known to be an order parameter in the striping phase transition of scalar φ 4 theory in noncommutative space, [8] and it may have relevance in this system as well.…”
Section: Jhep04(2001)039mentioning
confidence: 99%